PROFESSIONAL INTERDISCIPLINARY POSITION AND ROLE OF ACADEMIC CONSERVATOR-RESTORERS IN THEORY AND PRACTICE Methodical symbiosis and transdisciplinary cooperation using the example of the rebuilding and conservation of two Ottoman palaces in Istanbul - Jörg Breitenfeldt (Ochrona Dziedzictwa Kulturowego, 2019)
Professional ethics and tasks for conservator-restorers, in the preservation of cultural heritage in Europe today: considering the development of scientific conservation-restoration and the improvement of academic education for conservator-restorers in the course of the twentieth century, this paper will analyse the professional position of conservator-restorers and their role in the interdisciplinary cooperation with other professionals dealing with the preservation of cultural heritage. How does cooperation run in the planning stage and in theory and in practice on site? How can we differentiate between the specific professional contributions of conservator-restorers and the activities of other professionals in the field of heritage preservation? How can we improve communication and interdisciplinary cooperation between all professionals involved?